On the strange place of religion in contemporary art - Elkins, James (New York Routledge, 2004)
Can contemporary art say anything about spirituality? John Updike calls modern art "a religion assembled from the fragments of our daily life," but does that mean that contemporary art is spiritual? What might it mean to say that the art you make expresses your spiritual belief?On the Strange Place of Religion in Contemporary Art explores the curious disconnection between spirituality and current art. This book will enable you to walk into a museum and talk about the spirituality that is or is not visible in the art you see.